If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -66 = 6.6v Solving -66 = 6.6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6.6v' to each side of the equation. -66 + -6.6v = 6.6v + -6.6v Combine like terms: 6.6v + -6.6v = 0.0 -66 + -6.6v = 0.0 Add '66' to each side of the equation. -66 + 66 + -6.6v = 0.0 + 66 Combine like terms: -66 + 66 = 0 0 + -6.6v = 0.0 + 66 -6.6v = 0.0 + 66 Combine like terms: 0.0 + 66 = 66 -6.6v = 66 Divide each side by '-6.6'. v = -10 Simplifying v = -10
| 10z^6+9z^3-9=0 | | 7x-2=5.5 | | 16k^2-52k+30= | | 5x+3y=1500 | | 6x-7=4x+2 | | B-23=33 | | 30.6=5.1k | | 2x-21=x-10 | | 24-3(4-x)=-6 | | 14x-17x=6 | | 6b-4+b=-12 | | 9r-4(r+2)=5(2r-4)-18 | | y=3(x+1)(x-7) | | -13=2.8+a | | 4x^3-3x^2-10x+12=0 | | 2k^2-18k^2d^2= | | Y=-0.7x+4.9 | | 9-18x-15=-52x-126+10 | | -16x^2+50x+7=0 | | 4y-4+y+38=8y+40-5y | | 8x-17x=27 | | 2n=5n-21 | | .3(t-2)=.4 | | 18=c+5-2 | | H^2=32-4n | | N+0.7=3.9 | | 7-(4y-1)=3-5y | | X^2+7X+12=4X+14 | | (x+10)+(2x+20)+(4x-60)=180 | | y=-3(x+1)(x-8) | | 3(t-8)-3(4t-3)=-10(t+3)-3 | | 2y^2-12=10y |